How do introductory field biology students feel? Journal reflections provide insight into student affect. Issue 11 (15th November 2022) - Treibergs, Kira A.; Esparza, David; Yamazaki, Jeannie A.; Goebel, Marc; Smith, Michelle K.
Abstract: An understanding of both cognitive and affective domains of learning is critical to promoting undergraduate student success in biology. Field courses—which support student learning, observation, and experimentation in the outdoors—have been shown to be effective in supporting cognitive student outcomes. However, less is known about students' affective responses during field instruction. To better understand the affective domain in this course type, we asked students enrolled in a campus‐based introductory field biology course to engage in weekly reflective journaling over the course of a semester. We employed inductive and deductive coding of over 700 field journal reflections using the Model of the Affective Domain for the Geosciences as a conceptual basis. Informed by our results, we present a theoretically‐driven, five‐part Framework of Student Affect in Field Biology and in‐depth and novel insights into what students feel, believe, and value as they participate in an undergraduate field course. Our framework and coding results can be used by field course instructors to understand how to better design experiences that leave students feeling confident in their abilities, interested to learn more about nature, and empowered to persist in the discipline. Abstract : To better understand the affective domain of students participating in field biology, we coded over 700 journal reflections and developed a Framework of Student Affect in Field Biology. We share novel insights into student affect and make practical recommendations for instructors of undergraduate field biology courses.